The Effect Of Coconut Drain Flour And Black Potato Flour Substitution On Fiber Content And Organoleptics Of Beef Sausage: PENGARUH SUBSTITUSI TEPUNG AMPAS KELAPA DAN TEPUNG KENTANG HITAM TERHADAP KADAR SERAT DAN ORGANOLEPTIK SOSIS DAGING SAPI - abdi, haris (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
Sausage is one of the famous processed food products in Indonesia, sausage is obtained from a mixture of ground meat and flour or starch with the addition of spices, food additives that are put into sausage casings. The purpose of this study was to determine the fiber content and organoleptic in beef sausages that have been substituted with coconut pulp flour and black potato flour. The method used is the RAL method while to determine the fiber content in beef sausages using the gravimetric method, also using organoleptic tests with coconut pulp flour and black potato flour formulations. After this test, data analysis was carried out using one-way ANOVA. The results of the study on the effect of coconut pulp flour and black potato flour substitution on the fiber content and organoleptic of beef sausages obtained the highest fiber content at P2, which was 5.78%, while the lowest fiber content was at P0 at 3.67%. organoleptic test results in this study panelists preferred the color of P0 with a value of 3.86, the taste of P1 with a value of 3.5, the aroma of P1 with a value of 3.4, and the texture of P0 with a value of 3.26. which means that the difference in dosage in making sausages has a significant effect on the fiber content and organoleptic of beef sausages.